Ethics and geographical equity in health care. Issue 4 (1st August 2001) - Rice, Nigel; Smith, Peter C
Abstract : Important variations in access to health care and health outcomes are associated with geography, giving rise to profound ethical concerns. This paper discusses the consequences of such concerns for the allocation of health care finance to geographical regions. Specifically, it examines the ethical drivers underlying capitation systems, which have become the principal method of allocating health care finance to regions in most countries. Although most capitation systems are based on empirical models of health care expenditure, there is much debate about which needs factors to include in (or exclude from) such models. This concern with legitimate and illegitimate drivers of health care expenditure reflects the ethical concerns underlying the geographical distribution of health care finance.